USERS PERCEPTION OF THE EFFECTS OF COLOR ON WELLNESS AND HABITABILITY IN INTERIOR ARCHITECTURE: A case study of selected public buildings in Afe Babalola University, Ado Ekiti, Ekiti State. - Falusi, Tolulope; Benjamin , Afolabi (Aksen : Journal of Design and Creative Industry, 2024)
Psychologically, colors can produce certain feelings/ reactions, likewise in architecture, the colors of a building influence how users of the building feel. This in-depth study identified values of different colours used in the interior architecture of two purposively selected public buildings in Afe Babalola University, Ado-Ekiti (ABUAD). Effects of the colors on its users were analysed via descriptive statistics afterrandomly sampling 385 respondents. Slovin’s formula was used to get the population comprising staff and students of ABUAD. The study which employed a mixed method approach relied on a questionnaire, unstructured interview alongside observation as the primary data, and print materials among others. Findings from the study indicated that colors and good space complement other structural attributes for habitability while structural designs can also be used to strengthen human self-efficacy; needed as a form of wellness. Concerning colors used in the interior architecture, the visual comforts of staff and students in ABUAD have not been fully met. ABUAD Managements are therefore advised to consider the well-being of staff and students by addressing structures having dull and unimpressive colors; which are also poorly projecting her brand image. Architects/ Interior Designers should consider visual comfort when choosing colors of buildings for sustainable and maintained use. Keywords: Color, Habitability, Interior Architecture, Public Building, Visual Comfort & Wellness